Possibility of exact realization of silver tones in electrophotographic printing - Majnarić, Igor; Valdec, Dean; Vujčić, Đorđe (Journal of Graphic Engineering and Design, 2025)
Except for standard CMYK colors in high-quality printed products, designers often choose metallic silver tones. With this method, designers underline important segments and parts of printed publications. Silver applications today are mostly performed with expensive foil printing techniques or lithographic offset printing. However, the development of new Xerox electrophotographic machines has enabled the application of an additional silver toner that achieves a metallic effect of silver tones. In this paper, the possibility of successful realization of silver PANTONE 877C printed with the conventional offset printing (HUBER printing ink series Alchemy) and with silver Xerox emulsion aggregation (EA) toner was investigated. The test used 170 g/m2 gloss art printing paper printed on printing press Heidelberg GTO ZP 52 (offset printing conditions) and Xerox Versant 180 (electrophotographic printing conditions). Due to the easier modification of the electrophotographic press conditions (RIP Fiery FS 200), the printing was performed with two screenings (AM and FM distribution of printing elements in a halftone image). Due to the use of different silver pigments, two colorimetric measurement methods (M0 and M3 mode) were also analyzed. Colorimetric analysis (CIE LAB measurements and ΔE2000 color difference) showed that the silver halftones of Xerox EA toner also achieve large color changes ΔEmean>5. However, the PANTONE 877C tone will be better reproduced in full tone (ΔEOFF_Xerox = 4,2) while the rasterization process will achieve higher average tone deviations. By varying the Fiery RIP settings (FM-AM screening), a better imprint will be obtained with FM screening (average difference ΔEFM_AM = 0,64). Article history: Received (November 8, 2021); Revised (January 17, 2022); Accepted (January 20, 2022)